Stella Batts : superstar - Sheinmel, Courtney (Sheinmel, Courtney. Stella Batts, 2015)
Stella gets a chance to audition for her favorite television show when she meets a casting director who thinks she is perfect for the role, so she rehearses her lines until she know the part by heart, but the audition does not go as planned.